A Revised Code of Ordinances of the City of Tuscaloosa 170, § 420 (1885) - (:unkn) unknown (My University, 1885)
Prohibited carrying concealed any brass knuckles, slung-shot, or other weapon of like kind, or carries a rifle, shot gun walking cane. Violators fined not exceeding one hundred dollars, and may be imprisoned, or put to hard labor not exceeding sixty days.
Keywords: CARRY - CONCEALED